Income Inequality, Poverty and Public Health - Yousef Mohammadzadeh; Narges Taghizadeh; Elmnaz Nazariyan (Tehran University of Medical Sciences, 2017)
Background and Aim: When there is a big difference among income groups in a society, public health and healthcare costs may be affected through multiple channels. The present study aimed to investigate the effects of inequality and poverty (and other socio-economic characteristics of communities) on public health indicators and the structure of cost payments.  Materials and Methods: The present applied descriptive study has been conducted in 34 countries of the world (in terms of having regular data about income inequality) during 1995-2012 using a panel data approach. Eviews 9 software was used to estimate the models. The estimates were done in separate models for health indices and the related costs. Results: Income inequality and poverty on the one hand reduce public health, and on the other hand increase people's share of healthcare payments. Besides, the level of education promotes the community's public health and reduces direct out-of-pocket and private payments. However, population density in large cities leads to the increase of private health expenditure and direct out-of-pocket payments. Conclusion: On the path of economic development, we should pay special attention to income inequality among the members of society. Following inequality and higher relative poverty, mental and emotional problems deepen in society, and the health of individuals is seriously damaged. Byweakening the efficient management of health sector, this issue increases the individuals' direct out-of-pocket payments and, therefore, doubly deteriorates public health.